BENTUK DAN FUNGSI IKON LINGUAL DALAM TEKA-TEKI BERBAHASA INDONESIA - Basori, NFN (Balai Bahasa Kalimantan Tengah, 2019)
Puzzle is one form of verbal communication. Puzzles different from other types of communication. In puzzles, language is used in its function as a game. The language in puzzles used is usually used to tease, heckle, in packaged by slipping of tongue or phonetic forms of words. This research will explore the puzzle in its function as a game. Using the agih method using the determinant is an element of the language under study and a padan method that uses elements outside the language. The results of the study showed that there was creativity carried out by language users in using language in the form of puzzles. Konyol-humorik lingual icons in puzzles can be divided into several types, word play, punctuation, guesswork, questions, and discourse. The meaning in the form and type of the puzzle is very dependent on the context of its disclosure. This reinforces Halliday's statement that the text can never be released from its context.